PRIORITAS SINTESIS RATER AGREEMENT OBYEK DAN DAYA TARIK WISATA DI KABUPATEN BANYUWANGI - Jauhariyah, Nur Anim; Isnaini, Fajar; Syafa'at, Ahmad Munib (Ekosiana Jurnal Ekonomi Syari ah, 2022)
The tourism sector is one of the efforts in accelerating the increase in regional original income in Banyuwangi Regency in a sustainable manner during the pandemic and endemic period. This study aims to analyze the priority of rater agreement synthesis with Kendall's coefficient of concordance on objects and tourist attractions in optimizing local revenue in Banyuwangi Regency. This study uses a quantitative approach with the support of a qualitative approach through interviews and questionnaires to a number of experts. The sampling technique in this study was carried out by purposive sampling technique from respondents from the health office, the culture and tourism office, the Banyuwangi Regency Regional Development Planning Agency, the Healthy Banyuwangi Forum, and the Tourism Awareness Group. The analysis technique uses the Analytic Network Process (ANP). The results of the analysis show that the results of the analysis of the value of Kendall's coefficient of concordance W (rater agreement) is 0.95. The diversity of values given by each respondent contributed to the rater agreement score of 95%. The increase in the number of tourists and the length of stay of tourists occupy the highest priority for rater agreement synthesis at 36%. This confirms that optimistic tourism objects and attractions can be a trigger in boosting local revenue in the tourism sector in Banyuwangi Regency